PERSEPSI MAHASISWA JURUSAN MATEMATIKA TERHADAP GHIBAH DIGITAL DALAM PERSPEKTIF ETIKA KOMUNIKASI ISLAM - Munthe, Atiqah; Nabila Nasution; Syeila Fatiha; Magrifah Rizki Berutu; Hapni Laila Siregar (STKIP Subang, 2026)
The development of digital technology has transformed human communication patterns, but it also presents ethical challenges such as digital ghibah, which is categorized as a form of cyberbullying. This study aims to determine the perception of Mathematics Department students at Medan State University towards digital ghibah from the perspective of Islamic communication ethics. The research method used is quantitative descriptive with a sample of 35 students from the 2024 Mathematics Education program. Data was collected through a questionnaire containing 12 questions using a 2-point Likert scale and analyzed using Microsoft Excel. The results show that the level of students' knowledge, perception, and attitude towards digital ghibah is in the moderate category, with 20 respondents falling into this category. Additionally, Islamic communication skills on social media are also in the moderate category (53%), indicating that students have started to apply Islamic communication ethics values but the implementation is not yet fully consistent. The conclusion of this study is that it is necessary to strengthen digital literacy based on moral values and integrate character education to improve students' ethical awareness in communicating in the digital space.